PENGARUH PRODUCT QUALITY DAN SERVICE QUALITY TERHADAP KEPUASAN SERTA DAMPAK PADA LOYALITAS PELANGGAN (STUDI EMPIRIK MITRA 10 DEPOK, CIBUBUR DAN BOGOR) - Reagan Tambunan, Frans; Thalib, Supriadi; Miranda W, Agustinus (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
The purpose of this study is to analyze the influence product quality and service quality on Satisfaction and impact of customer loyalty (empirical study of Mitra 10 Depok, Cibubur Dan Bogor). This research uses non probability sampling by method purposive sampling against 330 respondents conducted on product quality and service quality on satisfaction and impact of customer loyalty (empirical study of Mitra 10 Depok, Cibubur Dan Bogor). This research uses analytical methods Structural Equation Modeling. The findings of this study indicate that (1) product quality influential significant against customer satisfaction (2) service quality influential significant against customer satisfaction (3) customer satisfaction influential significant against customer loyalty (4) product quality influential significant against customer loyalty (5) service quality influential significant against customer loyalty. For indirect influence produce findings that (6) product quality influential significant against customer loyalty through customer satisfaction (7) service quality influential significant against customer loyalty through customer satisfaction.